A method for preparing silver powder and silver paste for heterojunction solar cells

By mixing organic carrier, conductive silver powder and conductive silver nanomaterials in a dual planetary mixer, silver powder silver paste with good fluidity and printing performance is prepared, which solves the problems of poor leveling and insufficient printing properties of silver paste in the prior art. .

CN118762876BActive Publication Date: 2025-02-11SHENZHEN BROADSHINE NEW MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411238740.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2025-02-11
Estimated Expiration
2044-09-05

AI Technical Summary

Technical Problem

The content of micron-level silver powder in the conductive silver paste of existing heterojunction solar cells is high, resulting in high viscosity and poor leveling, which makes it impossible to adapt to fine line screen printing, and it is prone to grid line fracture, gate line width is too wide and gate line height is too low. The problem.

Method used

A silver powder silver paste preparation method is adopted, by mixing organic carrier, conductive silver powder, conductive silver nanomaterial and wetting dispersant in a double planetary mixer, and filtration of 500-600 mesh stainless steel wire mesh to obtain silver with good fluidity. Slurry.

Benefits of technology

The leveling, thixotropy and printing properties of silver paste are improved, so that silver paste can take into account good conductivity and printing performance, solve the problem of poor printing in the prior art, and is suitable for fine-wire screen printing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of silver paste for solar cells, and specifically to a method for preparing silver powder silver paste for heterojunction solar cells, which specifically comprises the following steps: 1) fully mixing and stirring an organic resin and a solvent; 2) sequentially adding a curing agent, a diluent and a accelerator, mixing and stirring to obtain an organic carrier mixture; 3) fully mixing the organic carrier mixture, a conductive silver powder and a conductive silver nanomaterial, and then adding a wetting dispersant to obtain a silver paste; 4) filtering the silver paste and then encapsulating it. The silver powder silver paste prepared in the present invention has good leveling, thixotropy and printability. Through the adjustment and combination of different epoxy resins, the organic carrier has good coating of the conductive silver powder and the conductive silver nanomaterial and the infiltration of the substrate. After curing, it shows good substrate adhesion performance and good conductivity, so that the solar cell has excellent electrical performance and photoelectric conversion efficiency, and the performance of the solar cell is enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of solar cell silver paste, in particular to a method for preparing silver powder silver paste for heterojunction solar cells. Background Art

[0002] Heterojunction solar cells use low-temperature curing silver paste, which is currently mainly epoxy resin, polyester resin and acrylic resin. With the development of technology, in order to improve conversion efficiency and reduce surface recombination, various battery manufacturers have adopted fine grid and dense grid technology (fine line screen printing) for battery cells. Fine grid and dense grid refers to the use of fine grid and dense grid technology to reduce the width of the grid line of solar cells to maximize the aspect ratio, thereby minimizing the shading area of ​​the battery and improving the overall efficiency of the battery.

[0003] For example, Chinese patent CN110176325A discloses a low-temperature calcined conductive silver paste for heterojunction solar cells and a preparation method thereof, wherein the silver paste comprises 85-92 parts by mass of a combination of silver powder, 6-12 The composite silver powder is composed of spherical silver powder and flaky silver powder; the average particle size of the spherical silver powder is 0.05 μm-3 μm; the average particle size of the flaky silver powder is 1 μm-3 μm; the preparation method is simple and reasonable in design, and the conductivity, printability, tension and other properties of the low-temperature baked heterojunction solar cell conductive silver paste prepared are excellent, meeting the requirements of the mainstream heterojunction solar cell screen printing grid in the market; however, due to the high content of micron-level silver powder in the silver paste, the viscosity is high, the leveling property of the paste is poor, and the printability is poor, which cannot adapt to fine-line screen printing, and is prone to printing problems such as broken grid lines, too wide grid lines and too low grid lines. Summary of the invention

[0004] In view of the problems existing in the prior art, the object of the present invention is to provide a method for preparing silver powder and silver paste for heterojunction solar cells.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] A method for preparing silver powder and silver paste for heterojunction solar cells specifically comprises the following steps:

[0007] 1) The organic resin and the solvent are fully mixed and stirred to obtain an organic carrier;

[0008] 2) Adding a curing agent, a diluent and an accelerator to the organic carrier in sequence, mixing and stirring for 7-10 hours in an oil bath at 80-85° C., to obtain an organic carrier mixture;

[0009] 3) Add the organic carrier mixture, conductive silver powder and conductive silver nanomaterial into a double planetary mixer, start the orbiting stirring blade and the self-rotating dispersing head, mix for 30-50 minutes, then add the wetting dispersant, and after mixing, vacuumize to remove bubbles to obtain a silver paste;

[0010] 4) Filter the silver paste through a 500-600 mesh stainless steel wire mesh and package the filtered silver paste.

[0011] As a further preferred embodiment of the present invention, the organic resin is selected from at least one of hydrogenated bisphenol A epoxy resin, hydrogenated bisphenol F epoxy resin, and hydrogenated bisphenol S epoxy resin, and its epoxy equivalent is 100-1000 g / eq;

[0012] The solvent is selected from at least one of butyl carbitol, butyl carbitol acetate, lauryl alcohol, terpineol, isophorone, propylene glycol methyl ether acetate, diethylene glycol butyl ether acetate, and diacetin;

[0013] The curing agent is selected from at least one of a blocked hexamethylene diisocyanate homopolymer, a blocked hydrogenated xylylene diisocyanate polymer, and a blocked isophorone diisocyanate polymer;

[0014] The diluent is selected from at least one of diethylene glycol ethyl ether acetate, diethylene glycol butyl ether acetate, dibasic acid ester, ethylene glycol acetic acid acetate, ethylene glycol butyl ether, and ethylene glycol phenyl ether;

[0015] The accelerator is selected from at least one of a blocked amine accelerator, a blocked ammonium salt, an organic tin, and an organic silver;

[0016] The wetting and dispersing agent is selected from polyester dispersants.

[0017] As a further preferred embodiment of the present invention, the components used in the silver paste are, by weight, 3-10 parts of organic resin, 2-7 parts of solvent, 3-5 parts of curing agent, 1.2-1.8 parts of diluent, 0.1-0.5 parts of accelerator, 0.2-0.6 parts of wetting and dispersing agent, 85-96 parts of conductive silver powder, and 10-18 parts of conductive silver nanomaterial.

[0018] As a further preferred embodiment of the present invention, the average particle size of the conductive silver powder is 0.05-3 μm.

[0019] As a further preferred embodiment of the present invention, the conductive silver nanomaterial is prepared by the following method:

[0020] 1) dispersing the composite silver nanorods in deionized water to obtain a dispersion, then adding oxalic acid solution and silver nitrate solution dropwise under magnetic stirring, stirring well to obtain a mixed solution;

[0021] 2) Under light-proof conditions, use sodium hydroxide solution and hydrochloric acid solution to adjust the pH value of the mixed solution to 10.0-10.5, and react at a constant temperature of 80-83° C. for 1-3 hours. After the reaction is completed, place the product in deionized water for dialyzing for 48-60 hours, centrifuge the product and dry it to obtain a conductive silver nanomaterial.

[0022] As a further preferred embodiment of the present invention, in step 1), the dispersion has a solid content of 1-3%;

[0023] The silver nitrate solution has a concentration of 200-280 mmol / L;

[0024] The oxalic acid solution has a concentration of 100-150 mmol / L;

[0025] The volume ratio of the oxalic acid, silver nitrate solution and dispersion is (0.1-0.3):1:(5-8).

[0026] As a further preferred embodiment of the present invention, in step 2), the sodium hydroxide solution has a concentration of 0.5-0.8 mol / L;

[0027] The hydrochloric acid solution has a concentration of 0.5-0.8 mol / L.

[0028] As a further preferred embodiment of the present invention, the composite silver nanorods are prepared by the following method:

[0029] 1) Weigh hexadecyltrimethylammonium chloride and pour it into a container, add sodium citrate aqueous solution, stir thoroughly, add chloroauric acid aqueous solution, stir thoroughly, quickly inject sodium borohydride solution, seal after thorough stirring, place in 80-85℃ oil bath and heat for 90-120min, take out and naturally cool to room temperature, then add to a centrifuge tube, add 7-10 times amount of deionized water, centrifuge, fully disperse in 7-10 times amount of deionized water, centrifuge again, repeat centrifugation 2-3 times, add to deionized water to obtain a gold seed solution with a solid content of 1-2%;

[0030] 2) Add the gold seed solution, ammonia water and hexadecyltrimethylammonium bromide to the container in sequence, stir thoroughly and place in a 50-56°C water bath, then add the silver nitrate aqueous solution and the ascorbic acid aqueous solution to the container at a rate of 0.75-0.80 mL / min, respectively, and continue to react for 15-30 minutes. After the reaction is completed, cool naturally to room temperature, centrifuge the product, repeatedly wash with deionized water, and dry to obtain composite silver nanorods.

[0031] As a further preferred embodiment of the present invention, in step 1), the ratio of hexadecyltrimethylammonium chloride, sodium citrate aqueous solution, chloroauric acid aqueous solution, and sodium borohydride is (0.15-0.20) g: (10-15) mL: (0.1-0.2) mL: (0.25-0.32) mL;

[0032] The sodium citrate aqueous solution has a concentration of 5-8 mmol / L;

[0033] The aqueous solution of chloroauric acid has a concentration of 25-28 mmol / L;

[0034] The sodium borohydride solution has a concentration of 25-28 mmol / L.

[0035] As a further preferred embodiment of the present invention, in step 2), the volume ratio of the gold seed solution, ammonia water, hexadecyltrimethylammonium bromide, silver nitrate aqueous solution, and ascorbic acid aqueous solution is (2-5): (0.3-0.7): (4.5-5.2): (4-6): (4-6);

[0036] The ammonia water has a concentration of 50-80 mmol / L;

[0037] The hexadecyltrimethylammonium bromide has a concentration of 0.4-0.7 mmol / L;

[0038] The silver nitrate aqueous solution has a concentration of 5-7 mmol / L;

[0039] The ascorbic acid aqueous solution has a concentration of 10-13 mmol / L.

[0040] Compared with the prior art, the present invention has the following beneficial effects:

[0041] In the present invention, Au nanodecahedron is used as a seed, and the molar ratio of ascorbic acid and silver nitrate as a reducing agent is adjusted, and then ammonia water is introduced to adjust the reduction potential of ascorbic acid. The addition of ammonia water reduces the content of byproduct silver halide, and controls the one-dimensional growth of silver nanorods together with hexadecyltrimethylammonium bromide, thereby synthesizing composite silver nanorods with a gold-silver heterostructure; the composite silver nanorods are introduced into a silver paste, and the composite nanorods, as a cylindrical structure, can transform the flow mode of conductive silver powder in the silver paste from sliding movement to rolling movement, thereby reducing the movement resistance of the conductive silver powder and improving its fluidity, thereby achieving the enhancement of the leveling property of the silver paste, so that the silver paste has good leveling property, thixotropy and screen printing performance; at the same time, in order to further The conductive ability of the silver paste is enhanced. In the present invention, while introducing the conductive silver powder, the composite silver nanorods are further processed. Through a reasonable ratio, oxalic acid is used as a reducing agent and silver nitrate is used as a silver source. Under light-proof conditions, silver nanoparticles are deposited on the composite silver nanorods through a hydrothermal reaction. The deposited nanoparticles increase the surface roughness of the composite silver nanorods to a certain extent, and enhance the bonding strength between the composite silver nanorods. The composite silver nanorods are connected to each other to form a mesh rod-shaped support structure in the silver paste, thereby constructing a conductive network in the silver paste, enhancing the conductivity of the silver paste, and making the solar cell have excellent electrical properties and photoelectric conversion efficiency, thereby achieving enhanced solar cell performance.

[0042] The silver powder and silver paste prepared in the present invention has good leveling, thixotropy and printability. Through the adjustment and combination of different epoxy resins, the organic carrier can cover the conductive silver powder and the conductive silver nanomaterial well and infiltrate the substrate well. After curing, the silver paste has good adhesion to the substrate and good conductivity, so that the solar cell has excellent electrical performance and photoelectric conversion efficiency, thereby achieving enhanced performance of the solar cell. DETAILED DESCRIPTION

[0043] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] In the embodiment of the present invention, the organic resin is selected from hydrogenated bisphenol A epoxy resin, and its epoxy equivalent is 1000g / eq; the solvent is selected from butyl carbitol; the curing agent is selected from blocked hexamethylene diisocyanate homopolymer; the diluent is selected from diethylene glycol ethyl ether acetate; the accelerator is selected from blocked amine accelerators; the wetting dispersant is selected from polyester dispersants; and the average particle size of the conductive silver powder is 2μm.

[0045] Example 1

[0046] A method for preparing silver powder and silver paste for heterojunction solar cells specifically comprises the following steps:

[0047] 1) Prepare the raw materials of each component according to the weight proportion, and mix 3 parts of organic resin and 2 parts of solvent thoroughly and stir to obtain an organic carrier;

[0048] 2) Add 3 parts of curing agent, 1.2 parts of diluent and 0.1 parts of accelerator to the organic vehicle in sequence, mix and stir well to obtain an organic vehicle mixture;

[0049] 3) Add the organic carrier mixture, 85 parts of conductive silver powder, and 10 parts of conductive silver nanomaterials into a double planetary mixer, start the orbiting stirring blade and the self-rotating dispersing head, mix for 30 minutes, then add 0.2 parts of wetting dispersant, and after mixing, vacuum to remove bubbles to obtain a silver paste;

[0050] Wherein, the preparation method of conductive silver nanomaterial is as follows:

[0051] 1) Weigh 0.15g of hexadecyltrimethylammonium chloride and pour it into a container, add 10mL of 5mmol / L sodium citrate aqueous solution, stir thoroughly, add 0.1mL of 25mmol / L chloroauric acid aqueous solution, stir thoroughly, quickly inject 0.25mL of 25mmol / L sodium borohydride solution, seal after thorough stirring, place in an 80℃ oil bath and heat for 90min, take out and naturally cool to room temperature, then add to a centrifuge tube, add 7 times the amount of deionized water, centrifuge, fully disperse in 7 times the amount of deionized water, centrifuge again, repeat centrifugation twice, add to deionized water, and obtain a gold seed solution with a solid content of 1%;

[0052] 2) 2 mL of gold seed solution, 0.3 mL of 50 mmol / L ammonia water, and 4.5 mL of 0.4 mmol / L hexadecyltrimethylammonium bromide were added to the container in sequence, stirred thoroughly, and placed in a 50°C water bath. Then, 4 mL of 5 mmol / L silver nitrate aqueous solution and 4 mL of 10 mmol / L ascorbic acid aqueous solution were added to the container at a rate of 0.75 mL / min, respectively. The reaction was continued for 15 min. After the reaction was completed, the mixture was naturally cooled to room temperature. The product was centrifuged, repeatedly washed with deionized water, and dried to obtain composite silver nanorods.

[0053] 3) dispersing the composite silver nanorods in deionized water to obtain a dispersion with a solid content of 1%, and then adding dropwise a 100 mmol / L oxalic acid solution and a 200 mmol / L silver nitrate solution under magnetic stirring, and controlling the volume ratio of the oxalic acid solution, the silver nitrate solution and the dispersion to be 0.1:1:5, and stirring well to obtain a mixed solution;

[0054] 4) Under light-proof conditions, adjust the pH value of the mixed solution to 10.0 using a 0.5 mol / L sodium hydroxide solution and a 0.5 mol / L hydrochloric acid solution, and react at a constant temperature of 80°C for 1 hour. After the reaction is completed, dialyze the product in deionized water for 48 hours, centrifuge the product and dry it to obtain a conductive silver nanomaterial.

[0055] Example 2

[0056] A method for preparing silver powder and silver paste for heterojunction solar cells specifically comprises the following steps:

[0057] 1) Prepare the raw materials of each component according to the weight parts, mix 7 parts of organic resin and 5 parts of solvent thoroughly and stir to obtain an organic carrier;

[0058] 2) Add 4 parts of curing agent, 1.5 parts of diluent and 0.3 parts of accelerator to the organic vehicle in sequence, mix and stir thoroughly to obtain an organic vehicle mixture;

[0059] 3) Add the organic carrier mixture, 90 parts of conductive silver powder, and 15 parts of conductive silver nanomaterials into a double planetary mixer, start the orbiting stirring blade and the self-rotating dispersing head, mix for 40 minutes, then add 0.5 parts of wetting dispersant, and after mixing, vacuumize to remove bubbles to obtain a silver paste;

[0060] Wherein, the preparation method of conductive silver nanomaterial is as follows:

[0061] 1) Weigh 0.18g of hexadecyltrimethylammonium chloride and pour it into a container, add 13mL of 7mmol / L sodium citrate aqueous solution, stir thoroughly, add 0.2mL of 26mmol / L chloroauric acid aqueous solution, stir thoroughly, quickly inject 0.3mL of 26mmol / L sodium borohydride solution, seal after thorough stirring, place in an 82℃ oil bath and heat for 100min, take out and naturally cool to room temperature, then add to a centrifuge tube, add 8 times the amount of deionized water, centrifuge, fully disperse in 8 times the amount of deionized water, centrifuge again, repeat centrifugation 3 times, add to deionized water, and obtain a gold seed solution with a solid content of 1.5%;

[0062] 2) 3 mL of gold seed solution, 0.5 mL of 70 mmol / L ammonia water and 5.0 mL of 0.5 mmol / L hexadecyltrimethylammonium bromide were added to the container in sequence, stirred thoroughly and placed in a 53°C water bath, and then 5 mL of 6 mmol / L silver nitrate aqueous solution and 5 mL of 12 mmol / L ascorbic acid aqueous solution were added to the container at a rate of 0.76 mL / min, respectively, and the reaction was continued for 25 min. After the reaction was completed, the mixture was naturally cooled to room temperature, the product was centrifuged, repeatedly washed with deionized water, and dried to obtain composite silver nanorods;

[0063] 3) dispersing the composite silver nanorods in deionized water to obtain a dispersion with a solid content of 2%, and then adding dropwise an oxalic acid solution with a concentration of 130 mmol / L and a silver nitrate solution with a concentration of 260 mmol / L under magnetic stirring, and controlling the volume ratio of the oxalic acid solution, the silver nitrate solution and the dispersion to be 0.2:1:7, and stirring well to obtain a mixed solution;

[0064] 4) Under light-proof conditions, adjust the pH value of the mixed solution to 10.5 using a 0.7 mol / L sodium hydroxide solution and a 0.7 mol / L hydrochloric acid solution, and react at a constant temperature of 82° C. for 2 h. After the reaction is completed, dialyze the product in deionized water for 52 h, centrifuge the product and dry it to obtain a conductive silver nanomaterial.

[0065] Example 3

[0066] A method for preparing silver powder and silver paste for heterojunction solar cells specifically comprises the following steps:

[0067] 1) Prepare the raw materials of each component according to the weight parts, and mix 10 parts of organic resin and 7 parts of solvent thoroughly and stir to obtain an organic carrier;

[0068] 2) Add 5 parts of curing agent, 1.8 parts of diluent and 0.5 parts of accelerator to the organic vehicle in sequence, mix and stir well to obtain an organic vehicle mixture;

[0069] 3) Add the organic carrier mixture, 96 parts of conductive silver powder, and 18 parts of conductive silver nanomaterials into a double planetary mixer, start the orbiting stirring blade and the self-rotating dispersing head, mix for 50 minutes, then add 0.6 parts of wetting dispersant, and after mixing, vacuumize to remove bubbles to obtain a silver paste;

[0070] Wherein, the preparation method of conductive silver nanomaterial is as follows:

[0071] 1) Weigh 0.20g of hexadecyltrimethylammonium chloride and pour it into a container, add 15mL of 8mmol / L sodium citrate aqueous solution, stir thoroughly, add 0.2mL of 28mmol / L chloroauric acid aqueous solution, stir thoroughly, quickly inject 0.32mL of 28mmol / L sodium borohydride solution, seal after thorough stirring, place in an 85℃ oil bath and heat for 120min, take out and naturally cool to room temperature, then add to a centrifuge tube, add 8 times the amount of deionized water, centrifuge, fully disperse in 8 times the amount of deionized water, centrifuge again, repeat centrifugation 3 times, add to deionized water, and obtain a gold seed solution with a solid content of 2%;

[0072] 2) 5 mL of gold seed solution, 0.7 mL of 80 mmol / L ammonia water and 5.2 mL of 0.7 mmol / L hexadecyltrimethylammonium bromide were added to the container in sequence, stirred thoroughly and placed in a 56°C water bath, and then 6 mL of 7 mmol / L silver nitrate aqueous solution and 6 mL of 13 mmol / L ascorbic acid aqueous solution were added to the container at a rate of 0.80 mL / min, respectively, and the reaction was continued for 30 min. After the reaction was completed, the mixture was naturally cooled to room temperature, the product was centrifuged, repeatedly washed with deionized water, and dried to obtain composite silver nanorods;

[0073] 3) dispersing the composite silver nanorods in deionized water to obtain a dispersion with a solid content of 3%, and then adding dropwise 150 mmol / L oxalic acid solution and 280 mmol / L silver nitrate solution under magnetic stirring, and controlling the volume ratio of oxalic acid solution, silver nitrate solution and dispersion to be 0.3:1:8, and stirring well to obtain a mixed solution;

[0074] 4) Under light-proof conditions, adjust the pH value of the mixed solution to 10.5 using a 0.8 mol / L sodium hydroxide solution and a 0.8 mol / L hydrochloric acid solution, and react at a constant temperature of 83° C. for 3 h. After the reaction is completed, dialyze the product in deionized water for 60 h, centrifuge the product and dry it to obtain a conductive silver nanomaterial.

[0075] Comparative Example 1: This comparative example is basically the same as Example 1, except that it does not contain conductive silver nanomaterials.

[0076] Comparative Example 2: This comparative example is basically the same as Example 1, except that step 1) is omitted in the preparation of the conductive silver nanomaterial.

[0077] Comparative Example 3: This comparative example is basically the same as Example 1, except that step 2) is omitted in the preparation of the conductive silver nanomaterial.

[0078] Comparative Example 4: This comparative example is basically the same as Example 1, except that step 3) is omitted in the preparation of the conductive silver nanomaterial.

[0079] Comparative Example 5: This comparative example is basically the same as Example 1, except that step 4) is omitted in the preparation of the conductive silver nanomaterial.

[0080] Test experiment:

[0081] Silver powder and silver paste samples were obtained by the preparation methods provided in Examples 1-3 and Comparative Examples 1-5, respectively. The volume resistivity was then detected by a multimeter. The silver paste was used for printing. The aspect ratio was detected by a 3D microscope. The printability was observed. The test results were prepared in Table 1.

[0082] Table 1

[0083]

[0084] It can be seen from Table 1 that the silver powder and silver paste in the present invention have excellent properties such as conductivity and printability, and can meet the requirements of silk-screen grid of mainstream heterojunction solar cells in the market.

[0085] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing silver powder and silver paste for heterojunction solar cells, characterized in that: The specific steps include: 1) The organic resin and the solvent are fully mixed and stirred to obtain an organic carrier; 2) Adding a curing agent, a diluent and an accelerator to the organic carrier in sequence, mixing and stirring for 7-10 hours in an oil bath at 80-85° C., to obtain an organic carrier mixture; 3) Add the organic carrier mixture, conductive silver powder and conductive silver nanomaterial into a double planetary mixer, start the orbiting stirring blade and the self-rotating dispersing head, mix for 30-50 minutes, then add the wetting dispersant, and after mixing, vacuumize to remove bubbles to obtain a silver paste; 4) Filter the silver paste through a 500-600 mesh stainless steel wire mesh and package the filtered silver paste; The conductive silver nanomaterial is prepared by the following method: The composite silver nanorods are dispersed in deionized water to obtain a dispersion, and then oxalic acid and silver nitrate solutions are added dropwise under magnetic stirring, and the mixture is stirred evenly to obtain a mixed solution; under light-proof conditions, a sodium hydroxide solution and a hydrochloric acid solution are used to adjust the pH value of the mixed solution to 10.0-10.5, and the mixture is reacted at a constant temperature of 80-83° C. for 1-3 hours. After the reaction is completed, the product is dialyzed in deionized water for 48-60 hours, and the product is centrifuged and dried to obtain a conductive silver nanomaterial; The composite silver nanorods are prepared by the following method: Weigh hexadecyltrimethylammonium chloride and pour it into a container, add sodium citrate aqueous solution, stir thoroughly, add chloroauric acid aqueous solution, stir thoroughly, quickly inject sodium borohydride solution, seal after thorough stirring, place in 80-85℃ oil bath and heat for 90-120min, take out and naturally cool to room temperature, then add to a centrifuge tube, add 7-10 times amount of deionized water, centrifuge, fully disperse in 7-10 times amount of deionized water, centrifuge again, repeat centrifugation 2-3 times, add to deionized water The gold seed solution, ammonia water and hexadecyltrimethylammonium bromide are sequentially added into a container, the mixture is stirred thoroughly and then placed in a 50-56°C water bath, and then the silver nitrate aqueous solution and the ascorbic acid aqueous solution are respectively added into the container at a rate of 0.75-0.80 mL / min, the reaction is continued for 15-30 min, and after the reaction is completed, the mixture is naturally cooled to room temperature, the product is centrifuged, and then repeatedly washed with deionized water and dried to obtain composite silver nanorods.

2. The method for preparing silver powder and silver paste for heterojunction solar cells according to claim 1, characterized in that: The organic resin is selected from at least one of hydrogenated bisphenol A epoxy resin, hydrogenated bisphenol F epoxy resin and hydrogenated bisphenol S epoxy resin, and its epoxy equivalent is 100-1000 g / eq; The solvent is selected from at least one of butyl carbitol, butyl carbitol acetate, lauryl alcohol, terpineol, isophorone, propylene glycol methyl ether acetate, diethylene glycol butyl ether acetate, and diacetin; The curing agent is selected from at least one of a blocked hexamethylene diisocyanate homopolymer, a blocked hydrogenated xylylene diisocyanate polymer, and a blocked isophorone diisocyanate polymer; The diluent is selected from at least one of diethylene glycol ethyl ether acetate, diethylene glycol butyl ether acetate, dibasic acid ester, ethylene glycol acetic acid acetate, ethylene glycol butyl ether, and ethylene glycol phenyl ether; The accelerator is selected from at least one of a blocked amine accelerator, a blocked ammonium salt, an organic tin, and an organic silver; The wetting and dispersing agent is selected from polyester dispersants.

3. The method for preparing silver powder and silver paste for heterojunction solar cells according to claim 1, characterized in that: The silver paste comprises the following components by weight: 3-10 parts of organic resin, 2-7 parts of solvent, 3-5 parts of curing agent, 1.2-1.8 parts of diluent, 0.1-0.5 parts of accelerator, 0.2-0.6 parts of wetting dispersant, 85-96 parts of conductive silver powder, and 10-18 parts of conductive silver nanomaterial.

4. The method for preparing silver powder and silver paste for heterojunction solar cells according to claim 1, characterized in that: The average particle size of the conductive silver powder is 0.05-3 μm.

5. The method for preparing silver powder and silver paste for heterojunction solar cells according to claim 1, characterized in that: The dispersion has a solid content of 1-3%; The silver nitrate solution has a concentration of 200-280 mmol / L; The volume ratio of the oxalic acid, silver nitrate solution and dispersion is (0.1-0.3):1:(5-8).

6. The method for preparing silver powder and silver paste for heterojunction solar cells according to claim 1, characterized in that: The sodium hydroxide solution has a concentration of 0.5-0.8 mol / L; The hydrochloric acid solution has a concentration of 0.5-0.8 mol / L.

7. The method for preparing silver powder and silver paste for heterojunction solar cells according to claim 1, characterized in that: The ratio of hexadecyltrimethylammonium chloride, sodium citrate aqueous solution, chloroauric acid aqueous solution, and sodium borohydride is (0.15-0.20) g: (10-15) mL: (0.1-0.2) mL: (0.25-0.32) mL; The sodium citrate aqueous solution has a concentration of 5-8 mmol / L; The aqueous solution of chloroauric acid has a concentration of 25-28 mmol / L; The sodium borohydride solution has a concentration of 25-28 mmol / L.

8. The method for preparing silver powder and silver paste for heterojunction solar cells according to claim 1, characterized in that: The volume ratio of the gold seed solution, ammonia water, hexadecyltrimethylammonium bromide, silver nitrate aqueous solution, and ascorbic acid aqueous solution is (2-5): (0.3-0.7): (4.5-5.2): (4-6): (4-6); The ammonia water has a concentration of 50-80 mmol / L; The hexadecyltrimethylammonium bromide has a concentration of 0.4-0.7 mmol / L; The silver nitrate aqueous solution has a concentration of 5-7 mmol / L; The ascorbic acid aqueous solution has a concentration of 10-13 mmol / L.

Citation Information

Patent Citations

  • Low-temperature roasting heterojunction solar cell conductive silver paste and preparation method thereof

    CN110176325A

  • Low-temperature conductive silver paste for HIT solar cell and preparation method thereof

    CN110136863A